G74(P) Hereditary Angioedema Type-2, individualised long term prophylaxis using C1 esterase inhibitor - Naseem, SR; Altamemi, S; Farsi, T (Archives of disease in childhood, 2016)
Hereditary angioedema (HAE) is an autosomal dominant disorder due to deficiency or malfunction of C1 inhibitor protein. It is characterised by recurrent angioedema episodes involving skin and mucosal surfaces. Rare attacks involving upper airway can be life threatening. Attacks are often unpredictable in onset, progression and severity. Deaths resulting from laryngeal angioedema are well recognised. Morbidity and mortality can successfully be reduced with prophylactic C1 esterase inhibitor (C1INH). This requires careful monitoring and individualised therapy. We describe a young girl who presented with recurrent angioedema episodes. The aim is to emphasise that careful monitoring and follow up can significantly influence the quality of care and therapeutic outcomes. She presented multiple times with angioedema involving head and neck region and required multiple paediatric Intensive care unit admissions with potential risk of air way compromise. Her C1 esterase inhibitor protein level was normal with significantly low level of C1 esterase inhibitor functional protein, consistent with type 2 hereditary angioedema. She was initially started on weekly prophylactic C1INH therapy. She continued to have breakthrough angioedema episodes with reduce frequency and severity. A careful review showed that most breakthrough attacks were on day six and day seven since last C1INH therapy. Weekly prophylactic therapy was changed to every 6th day and she was closely followed up. She did not have any breakthrough angioedema episodes on every sixth day C1INH therapy for the following 8 months. C1INH therapy is expensive and may not be available in resource limited centres. We conclude that it is important to make an individualised treatment plan to improve outcome when managing a patient with HAE based on best available sources and considering the needs of the individual patient.Key words:HAE, long term prophylaxis, C1INH.6th day regimen